Upaya Diplomasi Ekonomi Indonesia di Afrika Melalui Preferential Trade Agreement Indonesia Mozambik - Larasati, Langgeng; Aseilla, Dike (Keluwih: Jurnal Sosial dan Humaniora, 2021)
Abstract—In recent years, Indonesia has begun to expand trade cooperation in non-traditional markets, one of which is in the African region. Indonesia is active in cooperating with Africa because Africa is the "continent of hope" which contains a lot of material values that can be used wisely to increase the progress and prosperity of both parties. Indonesia has held two large meetings between Indonesia and Africa at the IAF (Indonesia Africa Forum) in 2018 followed by the IAID (Indonesia Africa Infrastructure Dialogue) on 20-21 August 2019. Mozambique is one of the countries on the African continent that is collaborating with Indonesia through the Indonesia-Mozambique Preferential Trade Agreement (IM-PTA) which was signed on 27 August 2019. This study attempts to describe the process of Indonesia's economic diplomacy in the IM-PTA. This research uses qualitative methods and literature study. The result of this research is that Indonesia's economic diplomacy efforts in IM-PTA have been carried out through seven stages of economic diplomacy. IM-PTA has now entered the ratification process and is expected to be the opening route for Indonesia's investment in Africa to increase economic growth in both countries. Keywords: economic diplomacy, IM-PTA, indonesia, mozambique Abstrak—Beberapa tahun belakangan, Indonesia mulai memperluas kerja sama perdagangan di pasar non-tradisional yang salah satunya berada di kawasan Afrika. Indonesia giat menjalin kerjasama dengan Afrika disebabkan bahwa Afrika sebagai “Benua Harapan” yang mana banyak terkandung nilai material yang dapat dimanfaatkan dengan bijak guna meningkatkan kemajuan dan kemakmuran kedua belah pihak. Indonesia telah menggelar dua pertemuan besar Antara Indonesia dan Afrika dalam IAF (Indonesia Africa Forum) pada 2018 kemudian disusul dengan IAID (Indonesia Africa Infrastructure Dialogue) pada 20-21 Agustus 2019. Mozambik merupakan salah satu negara di benua Afrika yang menjalin kerja sama dengan Indonesia melalui Preferential Trade Agreement Indonesia-Mozambik (IM-PTA) yang ditandangani pada 27 Agustus 2019. Penelitian ini berupaya untuk menguraikan proses diplomasi ekonomi Indonesia dalam IM-PTA. Penelitian ini menggunakan metode kualitatif dan studi kepustakaan. Hasil dari penelitian ini adalah upaya diplomasi ekonomi Indonesia dalam IM-PTA telah dijalankan melalui tujuh tahapan diplomasi ekonomi. IM-PTA kini sudah memasuki proses ratifikasi dan diharapkan dapat menjadi pembuka jalur investasi Indonesia di Afrika untuk meningkatkan pertumbuhan ekonomi di kedua negara. Kata kunci: diplomasi ekonomi, IM-PTA, indonesia, mozambik